Effects of Tualang Honey on pregnancy outcomes and reproductive system of offspring in rats exposed to maternal restraint stress - Mohd Nizam Haron
Exposure to stress during pregnancy has been shown to have adverse effects on pregnancy outcomes and may induce an impairment of reproductive function in male and female offspring. Honey is traditionally used by the Malays for enhancement of fertility. The aim of this study was to determine the effects of Tualang honey on pregnancy outcomes and reproductive system of offspring in rats exposed to restraint stress. In phase I study, pregnant rats were divided into four groups (n=10/group) i.e. control, honey, stress and honey+stress groups. Rats from honey and honey+stress groups received Tualang honey (1.2 g/kg body weight/day) oral1y from day I of pregnancy, meanwhile rats from stress and honey+stress groups were subjected to stress by repeated restraining (three times/day) from day 11 of pregnancy until delivery. Following delivery, pregnancy outcomes were assessed and dams were sacrificed at postpartum day 21 for assessments on corticosterone level and adrenal histology. In phase 2 study, 10 week old male rat offspring were mated with regular oestrus cycle female. Male sexual behaviour and reproductive performance were evaluated. After a week, male rats were sacrificed for assessment on reproductive parameters and oxidative stress markers in testis and hippocampus. In phase 3 study, oestrus cycle of 10 week old female offspring were assessed. Female rat offspring were then mated with fertile male to assess female sexual behaviour. At day 21 of pregnancy, female rats were sacrifice for assessment on reproductive parameters and oxidative stress markers in hippocampus. In dams, honey supplementation during restraint stress significantly improved gestation period and increased litter size. It also significantly improved corticosterone level and the thickness of adrenal zona fasciculata. In adult male rat offspring, honey supplementation during maternal restraint stress significantly increased testis and epididymis weights. It also significantly improved follicle-stimulating hormone, luteinising hormone and testosterone levels as well as percentages of abnormal sperm and sperm motility. In testicular histology, honey supplementation during pregnancy significantly increased seminiferous tubules diameter. In hippocampal histology, honey supplementation during maternal restraint- stress significantly increased the number of cells in CA1 and CA2, and also significantly decreased cell count in dentate gyrus. In testis, honey supplementation during maternal restraint stress significantly decreased malondialdehyde level and all antioxidant enzyme activities except catalase activity. Meanwhile in hippocampus, it significantly decreased malondialdehyde level and increased catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase and glutathione-S-transferase activities. In adult female rat offspring, honey supplementation during maternal restraint stress significantly restored oestradiol level. It also significantly increased the cell count in CA1, CA2 and CA3 of hippocampus. Honey supplementation during maternal restraint stress was also significantly decreased malondialdehyde level, increased total antioxidant capacity and reduced glutathione level, as well as significantly increased the levels of catalase, superoxide dismutase, glutathione peroxidase and glutathione reductase activities in hippocampus. In conclusion, this study might suggest that supplementation of Tualang honey during pregnancy seems to reduce the adverse effects of restraint stress on pregnancy outcomes as well as on reproductive system of male and female rat offspring. This effect could be probably due to the antioxidant property of Tualang honey which may work by reducing the corticosterone level and oxidative stress that leads to adverse effects of the reproductive system.